Surface-modified nano calcium carbonate as well as preparation method and application thereof

By self-assembling the organic layer on the surface of nano calcium carbonate, the surface-modified nano calcium carbonate was prepared by using the synergistic action of amphiphilic molecules and long-chain alkane compounds, the unmodified nano calcium carbonate in polyolefin film was solved. The lack of performance has achieved better compatibility and performance improvement.

CN119461448AActive Publication Date: 2025-02-18HUBEI TUOYING NEW MATERIAL CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411666074.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-18
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

Unmodified nano calcium carbonate leads to problems such as many interface defects, poor structural density, low strength, low toughness and poor water barrier properties in polyolefin films.

Method used

By self-assembling two organic layers on the surface of nano calcium carbonate, the surface-modified nano calcium carbonate prepared by using the synergistic action of amphiphilic molecules and long-chain alkane compounds has the advantages of concentrated size distribution, uniform particle size and high activation degree .

Benefits of technology

The compatibility of nano-calcium carbonate and polyolefin materials is improved, the mechanical properties, thermal stability and processing properties of composite materials are enhanced, and the lack of performance of the original nano-calcium carbonate in polyolefin films is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461448A_ABST
    Figure CN119461448A_ABST
Patent Text Reader

Abstract

The invention provides surface-modified nano calcium carbonate and a preparation method and application thereof.The preparation method includes the steps that an amphiphilic molecular solution is added into a Ca < 2 + > solution, an anhydrous sodium carbonate solution is slowly and dropwise added after ultrasonic mixing, a full stirring reaction is conducted, calcium carbonate precipitates are obtained, the pH value of the solution is adjusted to be neutral, the calcium carbonate precipitates are washed and dried, and the surface-modified nano calcium carbonate is obtained. And fully exchanging and reacting with a long-chain alkane compound in an exchanger to obtain the surface-modified nano calcium carbonate. The preparation method disclosed by the invention is rapid in activation and simple in process, and different from a traditional method for activating calcium carbonate by using a coupling agent, two organic layers are self-assembled on the surface of the nano calcium carbonate, so that the prepared surface-modified nano calcium carbonate has the advantages of concentrated size distribution, uniform particle size and high activation degree, is good in compatibility with a polyolefin material, and can be used for preparing a polyolefin material. The method can be widely applied to filling modification of high polymer materials such as plastics, rubber and coatings, and mechanical properties, thermal stability and processability of the materials are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano calcium carbonate, and in particular to a surface-modified nano calcium carbonate and a preparation method and application thereof. Background Art

[0002] Nano calcium carbonate is an ultrafine calcium carbonate with a particle size range of 1 to 500 nm. Due to its small particle size, changes in surface electronic structure and crystal structure, it has physical properties such as quantum size effect, surface effect and small size effect that heavy calcium carbonate does not have, and is widely used in the field of plastic processing. As an important inorganic filler for strengthening, toughening, increasing volume and weight, nano calcium carbonate materials are widely used in various organic polymer matrix materials. However, the direct application of unmodified nano calcium carbonate materials in, for example, polyolefin films will lead to problems such as many film interface defects, poor structural density, low strength, low toughness and poor water resistance. Therefore, it is necessary to modify the surface of nano calcium carbonate materials to improve the dispersibility of nano calcium carbonate particles and their compatibility with polyolefin matrices.

[0003] At present, the modification methods of nano calcium carbonate mainly include coupling agent modification, surfactant modification, grafting modification, inorganic material encapsulation modification and stereo modification. The patent with publication number CN118165547A discloses a nano calcium carbonate surface treatment agent and preparation method, including emulsion A and emulsion B, emulsion A includes vinyl-terminated polymethylsiloxane, hydrogen-containing polysiloxane, polyether-modified silicone oil, deionized water, etc.; emulsion B includes platinum metal catalyst emulsion. Although the nano calcium carbonate treated by the invention has a high degree of activation, the preparation process of active nano calcium carbonate is complicated and time-consuming, and there is no better treatment method for finer nano calcium carbonate.

[0004] In view of this, it is necessary to design an improved surface-modified nano-calcium carbonate and its preparation method and application to solve the above problems. Summary of the invention

[0005] In view of the defects of the above-mentioned prior art, the purpose of the present invention is to provide a surface-modified nano-calcium carbonate and a preparation method and application thereof. By self-assembling two organic layers on the surface of the nano-calcium carbonate, the surface-modified nano-calcium carbonate prepared has the advantages of concentrated size distribution, uniform particle size, high activation degree, and good compatibility with polyolefin materials.

[0006] To achieve the above object, the present invention provides a method for preparing surface-modified nano calcium carbonate, comprising the following steps:

[0007] S1. Configure Ca separately 2+ Solution, amphiphilic molecule solution, anhydrous sodium carbonate solution, set aside;

[0008] S2. To Ca2+ adding an amphiphilic molecule solution to the solution and ultrasonically mixing for a predetermined time;

[0009] S3. Slowly add anhydrous sodium carbonate solution to the solution obtained in step S2, stir the reaction thoroughly to obtain calcium carbonate precipitate, and adjust the pH value of the solution to neutral;

[0010] S4. Wash and dry the calcium carbonate precipitate obtained in step S3, and fully exchange and react with the long-chain alkane compound in an exchanger to obtain surface-modified nano calcium carbonate.

[0011] As a further improvement of the present invention, in step S1, the Ca 2+ The concentration of the solution is 0.1-1 mol / L; the concentration of the anhydrous sodium carbonate solution is 0.1-1 mol / L.

[0012] Furthermore, the amphiphilic molecule is a long-chain benzenesulfonic acid sodium salt or a long-chain stearic acid, and the Ca 2+ The solution is one of calcium chloride, calcium sulfate, calcium nitrate and calcium hydroxide.

[0013] As a further improvement of the present invention, in step S2, the Ca 2+ Ca in solution 2+ The molar ratio of the amphiphilic molecule to the amphiphilic molecule in the amphiphilic molecule solution is 1:(1-10).

[0014] The ultrasonic mixing time is 25 to 35 minutes.

[0015] As a further improvement of the present invention, in step S4, the calcium carbonate precipitate and the long-chain alkane compound are both transported to the exchanger by high-temperature air at 120-250° C.; the long-chain alkane compound is one of n-octane, n-nonane, n-decane, n-undecane to n-docosane and low-temperature paraffin. The mass ratio of the calcium carbonate precipitate to the long-chain alkane compound is 1:(0.05-0.5).

[0016] The present invention also provides a surface-modified nano-calcium carbonate, which is prepared by the above-mentioned preparation method of the surface-modified nano-calcium carbonate.

[0017] The invention discloses an application of surface-modified nano-calcium carbonate. The prepared surface-modified nano-calcium carbonate is melt-blended with polypropylene to prepare a PP / nano-calcium carbonate composite material. The filling mass of the surface-modified nano-calcium carbonate is 5-8%.

[0018] The beneficial effects of the present invention are:

[0019] The present invention provides a surface-modified nano calcium carbonate and a preparation method and application thereof, by 2+The amphiphilic molecule solution is added to the solution, ultrasonically mixed for a predetermined time, and then anhydrous sodium carbonate solution is slowly added dropwise, and the reaction is fully stirred to obtain a calcium carbonate precipitate, and the pH value of the solution is adjusted to neutral, and the calcium carbonate precipitate is washed and dried, and fully exchanged with a long-chain alkane compound in an exchanger to obtain a surface-modified nano calcium carbonate. The preparation method of the present invention has rapid activation and simple process. Different from the traditional method of activating calcium carbonate with a coupling agent, the present invention self-assembles two organic layers on the surface of nano calcium carbonate, and the surface-modified nano calcium carbonate prepared has the advantages of concentrated size distribution, uniform particle size, and high activation degree, and has good compatibility with polyolefin materials. It can be widely used in the filling modification of polymer materials such as plastics, rubbers, and coatings to improve the mechanical properties, thermal stability, and processing properties of the materials.

[0020] The present invention makes the surface of nano calcium carbonate have good hydrophilicity and hydrophobicity through the combined action of amphiphilic molecules and long-chain alkane compounds, which is conducive to dispersion in a polymer matrix. The interfacial compatibility between the surface-modified nano calcium carbonate and the polymer matrix is ​​improved, which is conducive to enhancing the mechanical properties of the composite material. At the same time, the addition of the surface-modified nano calcium carbonate helps to improve the thermal stability of the composite material, reduce the melt flow rate, and is conducive to the control of processing performance. The preparation method provided by the present invention is simple, the raw materials are easy to obtain, the production process is easy to control, it is conducive to reducing production costs, and it conforms to the development trend of green environmental protection.

[0021] The surface-modified nano calcium carbonate of the present invention can be applied to the enhancement, filling, modification and other aspects of polymer materials, and has a good application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a schematic structural diagram of the surface-modified nano-calcium carbonate provided by the present invention.

[0023] Figure 2 This is a SEM image of the surface-modified nano-calcium carbonate provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0025] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.

[0026] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.

[0027] The present invention provides a method for preparing surface-modified nano calcium carbonate, comprising the following steps:

[0028] S1. Configure Ca separately 2+ Solution, amphiphilic molecule solution and anhydrous sodium carbonate solution are set aside.

[0029] Specifically, Ca 2+ The concentration of the solution is 0.1-1 mol / L; the concentration of the anhydrous sodium carbonate solution is 0.1-1 mol / L. 2+ The solution is one of calcium chloride, calcium sulfate, calcium nitrate and calcium hydroxide.

[0030] The amphiphilic molecule is preferably a long-chain benzenesulfonic acid sodium salt or a long-chain stearic acid.

[0031] The long-chain benzene sulfonic acid sodium salt is preferably sodium dodecylbenzene sulfonate; the long-chain benzene sulfonic acid sodium salt has good water solubility and can form a stable micelle structure in water. The sulfonic acid group can provide negative charge, which is helpful to disperse and stabilize the nanoparticles.

[0032] Long-chain stearic acids are preferably hexadecanoic acid and octadecanoic acid; long-chain stearic acids are highly hydrophobic, which helps to improve the hydrophobicity of nano-calcium carbonate and the dispersibility in non-polar media.

[0033] S2. To Ca 2+ The amphiphilic molecule solution is added to the solution and ultrasonically mixed for a predetermined time.

[0034] Specifically, Ca 2+ The molar ratio of the amphiphilic molecule to the amphiphilic molecule is 1:(1-10). The ultrasonic mixing time is 25-35 minutes.

[0035] Amphiphilic molecules form micelles in water, where their long hydrophobic chains aggregate together. These molecules can stabilize Ca 2+ ions, with Ca 2+ The amphiphilic molecules can also help long-chain alkane compounds to be more effectively adsorbed to the surface of nano calcium carbonate during subsequent surface modification.

[0036] S3. Slowly add anhydrous sodium carbonate solution to the solution obtained in step S2, stir the reaction thoroughly to obtain calcium carbonate precipitate, and adjust the pH value of the solution to neutral.

[0037] Specifically, the anhydrous sodium carbonate solution and the Ca 2+ The molar ratio of the solution is preferably 1: 1. Adjusting the pH of the solution to neutral can ensure the stable precipitation of calcium carbonate and avoid the formation of other forms of calcium carbonate or by-products.

[0038] S4. Wash and dry the calcium carbonate precipitate obtained in step S3, and fully exchange and react with the long-chain alkane compound in an exchanger to obtain surface-modified nano calcium carbonate.

[0039] Specifically, the long-chain alkane compound is preferably one of n-octane, n-nonane, n-decane, n-undecane to n-docosane and low-temperature paraffin. The calcium carbonate precipitate and the long-chain alkane compound are both transported to the exchanger by high-temperature air at 120 to 250°C. This temperature range can promote the effective interaction between the alkane molecules and the surface of calcium carbonate, while avoiding excessively high temperatures that cause alkane decomposition or calcium carbonate structure destruction. The mass ratio of calcium carbonate precipitate to the long-chain alkane compound is preferably 1: (0.05 to 0.5). The long-chain alkane compound will adsorb to the surface of calcium carbonate to form a hydrophobic layer, thereby giving the nano calcium carbonate specific surface properties.

[0040] The invention discloses an application of surface-modified nano-calcium carbonate. The surface-modified nano-calcium carbonate is melt-blended with polypropylene (PP) to prepare a PP / nano-calcium carbonate composite material, wherein the filling mass of the surface-modified nano-calcium carbonate is 5-8%.

[0041] The interfacial compatibility between surface-modified nano-calcium carbonate and polypropylene is improved, the agglomeration of nano-particles is reduced, and the nano-particles can be evenly dispersed in the polymer matrix. The modifier forms a bonding layer on the surface of nano-calcium carbonate, which enhances the interaction between nano-particles and polymer molecules, thereby improving the mechanical properties of the composite material. Nano-calcium carbonate particles play a role in hindering the movement of molecular chains in the composite material. When the composite material is heated, the nano-particles can hinder the movement of polymer chain segments, thereby improving thermal stability. An appropriate amount of nano-calcium carbonate particles can act as stress concentration points, triggering the yield and plastic deformation of the surrounding polymer matrix, thereby absorbing more energy and improving the impact toughness of the composite material. Nano-calcium carbonate with a filling mass of 5-8% can ensure the improvement of the performance of the composite material without excessively reducing its processing performance and toughness. Too high a filling amount may cause agglomeration of nano-particles and processing difficulties, while too low a filling amount may not be enough to significantly improve the performance of the composite material.

[0042] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0043] Example 1

[0044] Embodiment 1 provides a method for preparing surface-modified nano calcium carbonate, comprising the following steps:

[0045] S1. Prepare a 0.5 mol / L calcium chloride solution and a 0.5 mol / L anhydrous sodium carbonate solution;

[0046] S2. 500 ml of calcium chloride solution was placed in a beaker, dodecylbenzenesulfonic acid solution was added, and ultrasonic mixing was performed for 30 min;

[0047] S3. Slowly add 500 ml of anhydrous sodium carbonate solution and stir the reaction thoroughly to obtain calcium carbonate precipitate, and adjust the solution to neutral;

[0048] S4. Wash and dry the calcium carbonate precipitate, use 180°C hot air to transport the calcium carbonate precipitate to the exchanger, gasify n-octane with 180°C high-temperature air and transport it to the exchanger for full exchange reaction to obtain surface-modified nano calcium carbonate material. Figure 1 As shown in the figure, the amphiphilic small molecules are distributed around the calcium carbonate, and the long-chain alkyl molecules surround the periphery of the amphiphilic small molecules, forming two organic layers. The surface-treated calcium carbonate particles are easier to disperse in the polymer matrix, thereby improving the processing performance of the composite material and the physical and mechanical properties of the final product. Figure 2 As shown, the prepared surface-modified nano-calcium carbonate has a concentrated size distribution and a uniform particle size of 50 to 100 nm.

[0049] Embodiment 2-8

[0050] Examples 2-8 respectively provide a method for preparing surface-modified nano-calcium carbonate. Compared with Example 1, the only difference is that the type of amphiphilic molecules, the type of long-chain alkyl and the amount added are different, as shown in Table 1. Other experimental parameters and conditions are basically the same as those in Example 1 and will not be repeated here.

[0051] Table 1 Comparison of experimental parameters

[0052]

[0053] Comparative Example 1

[0054] Comparative Example 1 provides a method for preparing surface-modified nano-calcium carbonate. Compared with Example 1, the only difference is that no long-chain alkane compound is added in step S4. Other experimental parameters and conditions are basically the same as those in Example 1 and are not repeated here.

[0055] Comparative Example 2

[0056] Comparative Example 2 provides a method for preparing surface-modified nano-calcium carbonate, wherein the nano-calcium carbonate is treated with a coupling agent, comprising the following steps: surface-treating the prepared nano-calcium carbonate with a titanate coupling agent, wherein the mass ratio of the nano-calcium carbonate to the titanate coupling agent is 1:0.1, and other experimental parameters and conditions are basically the same as those in Example 1, which will not be repeated here.

[0057] The characterization of nano calcium carbonate includes oil absorption value, water absorption rate, and activation degree. The test is carried out according to the test standard of nano calcium carbonate GB / T 19590-2011. The test results are shown in Table 2, where the oil absorption value is the amount of DOP (dioctyl phthalate) absorbed per 100 grams of sample; the water absorption rate is the test result after the sample is continuously exposed to 85°C and 95% humidity for 72 hours.

[0058] Table 2 Test results of embodiments and comparative examples

[0059] project Oil absorption value (g) Water absorption (%) Activation degree (%) Example 1 10.85 0.25 98.78 Example 2 10.29 0.19 99.01 Example 3 9.87 0.13 99.26 Example 4 9.43 0.08 99.86 Example 5 13.45 0.18 95.69 Example 6 12.78 0.15 96.28 Example 7 11.97 0.11 97.88 Example 8 11.12 0.09 98.45 Comparative Example 1 49.57 0.76 15.78 Comparative Example 2 31.29 0.51 85.89

[0060] As can be seen from Table 2, under the same conditions, the amphiphilic small molecules of long-chain stearic acid and long-chain alkylbenzene sulfonic acid have a good surface treatment effect on nano-calcium carbonate. With the increase of the content of amphiphilic small molecules, the oil absorption value and water absorption rate of nano-calcium carbonate gradually decrease, and the activation degree gradually increases. This is because the content of the modified molecules increases, and the modification effect on nano-calcium carbonate is also better. Amphiphilic small molecules can be adsorbed on the surface of nano-calcium carbonate to form a modified layer. The hydrophilic end and hydrophobic end of these molecules can interact with water and oily substances respectively, thereby changing the surface properties of nano-calcium carbonate. With the increase of the content of amphiphilic small molecules, more nano-calcium carbonate surfaces are modified, reducing the direct contact area with oil or water, so the oil absorption value and water absorption rate will gradually decrease. With the increase of molecular weight of amphiphilic molecules and molecular weight of long-chain alkane modifiers, the oil absorption value and water absorption rate of nano-calcium carbonate gradually decrease, and the activation degree gradually increases. This is because the amphiphilic molecules and activated molecules with large molecular weight have better coating effect on calcium carbonate, and the covering layer of molecules on the surface of nano-calcium carbonate is more complete and dense, which further reduces the oil absorption value and water absorption rate and improves the activation degree.

[0061] Comparative Example 1 does not add long-chain alkane compounds, and the oil absorption value and water absorption rate are significantly increased, and the activation degree is reduced, indicating that there is a synergistic effect between the long-chain alkane compound and the amphiphilic molecule, and the amphiphilic molecule is combined with the surface of the nano-calcium carbonate through its hydrophilic end and hydrophobic end, and the long-chain alkane compound enhances the formation of the hydrophobic layer, making the modified layer more complete and dense, and the long-chain alkyl can reduce the interaction between the nanoparticles and the oily substance, thereby reducing the oil absorption value. The synergistic effect of the amphiphilic molecule and the long-chain alkane compound can reduce the hydrophilicity of the surface of the nano-calcium carbonate, thereby reducing the water absorption rate, and the long-chain alkane compound also helps the amphiphilic molecule to be better anchored on the surface of the nano-calcium carbonate, thereby improving its activation degree. Comparative Example 2 uses a traditional coupling agent to activate calcium carbonate, and the oil absorption value is high and the activation degree is low, indicating that the method of the present application is better for the surface modification effect of nano-calcium carbonate.

[0062] The nano calcium carbonate prepared in the embodiment and the comparative example was melt blended and filled with polypropylene, wherein the filling mass of the nano calcium carbonate was 5%, and then granulated by twin screw extruder to prepare standard test specimens, and the mechanical properties of the modified composite material were tested. The test standard refers to the second part of the test conditions for molded and extruded plastics in the determination of tensile properties of plastics GB / T1040.2. The test results are shown in Table 3.

[0063] Table 3 Performance test results of composite materials

[0064]

[0065]

[0066] As can be seen from Table 3, when the amphiphilic molecule is sodium dodecylbenzene sulfonate, as the concentration of the amphiphilic molecule increases, the tensile yield stress and tensile fracture stress of the modified polypropylene are increased compared with the unmodified polypropylene material. This is because the polypropylene material added with inorganic powder has a better reinforcing effect on the polypropylene material with activated calcium carbonate, and the rigidity of the composite material is enhanced; similarly, the increase of long-chain alkyl modifiers will also enhance the activation effect of calcium carbonate and the modification effect on the composite material is also better. As can be seen from Examples 5-8, hexadecanoic acid and octadecanoic acid can affect the performance of the composite material, and both have a certain strengthening and toughening effect; as the number of carbon atoms in the long-chain alkyl increases, the strengthening and toughening effect on the polypropylene / calcium carbonate composite material is more obvious.

[0067] In summary, the present invention provides a surface-modified nano-calcium carbonate and its preparation method and application. Different from the traditional method of activating calcium carbonate with a coupling agent, the surface-modified nano-calcium carbonate prepared by the present invention has the advantages of concentrated size distribution, uniform particle size and high activation degree; the preparation method of the present invention has the advantages of rapid activation and simple process; different from the traditional modification methods of coupling agents and surfactants, the present invention self-assembles two organic layers on the surface of nano-calcium carbonate, which has the advantages of high activity and good compatibility with polyolefin materials. The surface-modified nano-calcium carbonate of the present invention can be applied to the enhancement, filling, modification and other aspects of polymer materials, and has a good application prospect.

[0068] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing surface-modified nano calcium carbonate, characterized in that: The following steps are involved: S1. Configure Ca separately 2+ Solution, amphiphilic molecule solution, anhydrous sodium carbonate solution, set aside; S2. To Ca 2+ adding an amphiphilic molecule solution to the solution and ultrasonically mixing for a predetermined time; S3. Slowly add anhydrous sodium carbonate solution to the solution obtained in step S2, stir the reaction thoroughly to obtain calcium carbonate precipitate, and adjust the pH value of the solution to neutral; S4. Wash and dry the calcium carbonate precipitate obtained in step S3, and fully exchange and react with the long-chain alkane compound in an exchanger to obtain surface-modified nano calcium carbonate.

2. The method for preparing surface-modified nano-calcium carbonate according to claim 1, wherein In step S1, the Ca 2+ The concentration of the solution is 0.1-1 mol / L; the concentration of the anhydrous sodium carbonate solution is 0.1-1 mol / L.

3. The preparation method of surface-modified nano calcium carbonate according to claim 2, characterized in that, The amphiphilic molecules in the amphiphilic molecule solution are long-chain benzenesulfonic acid sodium salts or long-chain stearic acids.

4. The preparation method of surface-modified nano calcium carbonate according to claim 2, characterized in that, The Ca 2+ The solution is one of calcium chloride, calcium sulfate, calcium nitrate and calcium hydroxide.

5. The method for preparing surface-modified nano-calcium carbonate according to claim 1, characterized in that: In step S2, the Ca 2+ Ca in solution 2+ The molar ratio of the amphiphilic molecule to the amphiphilic molecule in the amphiphilic molecule solution is 1:(1-10).

6. The method for preparing surface-modified nano-calcium carbonate according to claim 5, characterized in that: The ultrasonic mixing time is 25 to 35 minutes.

7. The method for preparing surface-modified nano-calcium carbonate according to claim 1, characterized in that: In step S4, the calcium carbonate precipitate and the long-chain alkane compound are transported to the exchanger via high-temperature air at 120-250°C.

8. The method for preparing surface-modified nano-calcium carbonate according to claim 7, characterized in that: The long-chain alkane compound is one of n-octane, n-nonane, n-decane, n-undecane to n-docosane and low-temperature paraffin; the mass ratio of the calcium carbonate precipitate to the long-chain alkane compound is 1:(0.05-0.5).

9. A surface-modified nano calcium carbonate, characterized in that: The surface-modified nano calcium carbonate is prepared by the preparation method of any one of claims 1 to 8.

10. An application of the surface-modified nano calcium carbonate according to claim 9, characterized in that: The surface-modified nano-calcium carbonate is melt-blended with polypropylene to prepare a PP / nano-calcium carbonate composite material, wherein the filling mass of the surface-modified nano-calcium carbonate is 5-8%.

Citation Information

Patent Citations

  • Production process of ultrafine calcium carbonate powder

    CN111333096A

  • Hydrophobic calcium carbonate and preparation method thereof

    CN111439770A

  • Process for the preparation of surface-treated calcium carbonate material and use of same in the control of organic material in an aqueous medium

    US20130192784A1